Gastroesophageal reflux disease and functional dyspepsia: clinical efficacy and safety of prokinetic choice - D. I. Trukhan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present literature data on application of prokinetics at gastroesophageal reflux disease and functional dyspepsia.Summary. Gastroesophageal reflux disease and functional dyspepsia are considered to be the most common gastroenterological diseases. Motility disorder of gastroesophageal zone plays a leading part in pathogenesis of these diseases that assumes application prokinetics as a baseline therapy. Itopride hydrochloride has advantage over other prokinetics by three key parameters: double mechanism of action, absence of drug interactions and serious side effects.